Motif, Intensitas Mendengarkan, dan Kepuasan Pendengar Kopi Pagi Radio Solopos - Wening Palupi Ningtyas Putri; Firdastin Ruthnia Yudiningrum (Jurnal Komunikasi Massa, 2024)
Radio is the media people’s choice to fulfill their needs for information and entertainment. The process of disseminating information on radio is very extensive and fast. The progress and increase in internet use in Indonesia, such as the emergence of digital music streaming platforms, has influenced the existence of radio. However, this does not significantly threaten the existence of radio, because radio has the advantage of building intimacy between announcer and radio listeners. The news radio broadcasts lost their popularity a little, because listeners were more interested in music broadcasts. The urgency of this research is to determine the active response of Radio Solopos listeners before, during, and after listening to Kopi Pagi program. This research uses a positivism paradigm with correlational research methods, and using the SPSS version 26 as statistical test tool. In this research used Rank Kendall correlation testing. This research took the average population of active listeners of Radio Solopos news programs, namely Kopi Pagi, Zona 103,and Lintas Kota, as 276 listeners. Then, the sampling technique in this research used purposive sampling. The results of research correlation testing show that there is a significant between motive and intensity of radio listening, and gratification sought of listeners on Kopi Pagi program. Then, the entertainment indicator is the main hope of listeners for choose to listening of Kopi Pagi to fulfill their needs in terms of filling free time, conveying their hobbies, eliminating boredom, and distracting themselves from work problems. This research is limited to one news program in Radio Solopos namely Kopi Pagi. The hope is that in the next research, that it will involve other Radio Solopos news programs, namely Zona 103 and Lintas Kota, so that the results of gratification sought of listeners on Radio Solopos news programs can be comprehensive for all news programs.